Effects of season and cohort on the haematology of the geometric tortoise Psammobates geometricus. - Walton, Shasheen (University of the Western Cape, 2015)
Magister Scientiae (Biodiversity and Conservation Biology) - MSc (Biodiv and Cons Biol) === The geometric tortoise is one of the world‟s rarest terrestrial tortoises and is endemic to the Southwestern Cape, South Africa. There has been cause for conservation concern for Psammobates geometricus, yet as is common for many species, quantitative physiological research has been lacking. Considering the important role of red blood cells in oxygen circulation, and the role of white blood cells in immune resistance, blood profiles have been used across taxa as a reliable indicator of health status and physiological processes. Forming part of a larger chelonian conservation programme in South Africa, I studied the haematological changes in P. geometricus, to better understand their physiological responses to changes in climatic conditions. Sampled peripheral blood from males, females and juveniles of the largest known wild geometric tortoise population over four seasons (spring, summer, autumn and winter) from August 2000 to June 2001. Blood samples were used to make smears and determine red cell count (RCC), packed cell volume (PCV), haemoglobi concentration (Hb), red cell indices and differential white cell counts. Digital imaging analysis was used for the histological evaluation of stained blood smears, including descriptions of red and white blood cell morphologies, as well as erythrocyte developmental stages. In the cooler periods, geometric tortoises showed low Hb and mean cell haemoglobin concentration values. Erythrocytes were larger and rounder in winter and spring, which were likely due to hydration states. In addition, increased numbers of immature erythrocytes in circulation suggested an erythropoietic response in winter and spring. This regenerative response is common in reptiles emerging from periods of limited activity and is associated with increasing primary production following rainfall events. In the following summer and autumn, increased mean cell haemoglobin concentrations suggested elevated metabolic rates influenced by rising temperatures. This would seem pertinent to meet the extra physical demands associated with foraging effort in the season characterised with limited water and food supply, and mating behaviour, which occurs in the summer. Low body conditions across all cohorts provided evidence for nutrition stress, while erythrocyte size, shape and degenerative responses indicated dehydration stress. Physiological responses to seasonal influences are specific to growth or reproductive demands and differed for each cohort. Males experienced increased Hb, PCV, RCC, and erythrocyte sizes in summer and autumn, which relate to the erythropoieticstimulating effects of androgens. Female erythropoietic cycles in spring accommodate the increased metabolic demands of increased foraging needed for a larger body size and egg production, and again in autumn again for vitellogenesis. Juvenile tortoises showed minimal differences, and could indicate species-specific responses to environmental changes. A spring-related erythropoiesis was observed in juveniles while during summer and autumn, juveniles showed less evidence for dehydration stress than in adults. No haemoparasites were observed in peripheral blood. Seven leukocyte types were identified and included heterophils, eosinophils, basophils, lymphocytes, plasma cells, monocytes and azurophils, in addition to thrombocytes. Heterophils were the most abundant leukocyte, followed by lymphocytes and eosinophils while monocytes and basophils were equally low; plasma cells and azurophils were rare. Heterophil counts were higher in spring than in summer and autumn, and in summer, were more abundant in females than in juveniles. Eosinophil counts were low in spring for all cohorts, and additionally, female and juvenile counts were low in summer. Eosinophils in juveniles were significantly lower than in adults in winter and spring. Lymphocyte numbers increased in autumn for all cohorts, while summer counts were higher in juveniles than in adults. Basophils and monocytes showed minimal seasonal changes, although basophil counts in females in winter tended to be high. Thrombocytes were lowest in spring for all cohorts. Understanding the physiological responses associated with seasonal changes and for each cohort is critical for effective chelonian conservation management. Results obtained from this study indicate a clinically healthy population of Psammobates geometricus and represented the first of this kind to establish baseline haematological reference data for this Critically Endangered tortoise species.